Azathioprine in the Treatment of Multiple Sclerosis: A Single Center Experience from Nepal - Rajbhandari, Reema; Shakya, Sasa; Kumar Yadav, Jayant; Tamrakar, Abhishek; Kumar Jaiswal, Sandip; Rajbhandari, Pravesh; Chandra, Avinash (Annapurna Journal of Health Sciences, 2023)
Introduction: Azathioprine is used as an off - label drug for the treatment of multiple sclerosis. It is one of the oldest and most widely used immunosuppressants that targets T and B lymphocytes and thus reduces the relapse and slows down the disease progression with the almost same efficacy as the other disease modifying drugs for multiple sclerosis. But due to its side effect profile it isn’t used as a standard choice of treatment. However, its cost effectiveness and oral route of administration makes it a drug of choice in a low socioeconomic country. This paper highlights the diagnosis of Multiple Sclerosis based on McDonald’s criteria and treatment with Azathioprine. Methods: It is a retrospective analysis was conducted among 32 patients suffering from Multiple sclerosis and treated with Azathioprine at tertiary neurological institue.Patients outcome was also documented reaching them individually. Results: Among 19 patients all were female with highest prevalence among age group of 30-39 years old. 60% had relapsing remitting Multiple sclerosis, 45% of the patients present with ocular symptoms followed by 31% patients with lower limb weakness and spasticity. 30% did not develop any relapse, 15.8% patients developed one episode of relapse, 21.1% patients relapsed twice while 21.1% patients relapsed thrice during the study period. 85% patients showed signs of improvements with Azathioprine therapy in terms of decreased neurological residual deficits and less complication. Conclusion: Azathioprine shows improvement, slows the rate of relapse with minimal evidence of side effects and no evidence of malignancy in patients with multiple sclerosis.